1999
DOI: 10.1002/(sici)1520-6343(1999)5:3<179::aid-bspy7>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

5,10,15,20-Tetrakis(4-N-methylpyridyl)porphyrinatopalladium(II) as a differentiation probe for sensing binding modes with B-DNA duplexes: Electronic MCD and CD spectra

Abstract: We report our detailed electronic MCD, CD, and optical spectroscopic measurements and analysis of the porphyrin Soret (B0) region of four‐coordinate 5,10,15,20‐tetrakis(4‐N‐methylpyridyl)porphyrinatopalladium(II), PdP(4), and its bound states with B‐DNA duplexes poly(A‐T)2, poly(G‐C)2, and calf thymus DNA (CT DNA). For system PdP(4)/poly(A‐T)2 it was possible to conclude that the porphyrin is bound edge‐on in the major groove, specifically at the 5′AT3′ site. For this orientation the porphyrin's electric dipol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
7
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 50 publications
(59 reference statements)
4
7
0
Order By: Relevance
“…The distinctive changes in UV-ECD support our observations in the Soret spectral region that TMPyP interacts with (dA-dT) 10 by at least two binding modes: in addition to external binding mode to the phosphate backbone, which does not change the oligonucleotide structure significantly, another binding mode took place (for example an edge-on minor groove or a major groove binding took place as was suggested in [18]) which disturbs the arrangement of oligonucleotide bases [6]. Indeed, at the ratio 6/1, the UV-ECD spectrum reflects the transition state between B-and modified Z-forms of the (dA-dT) 10 [17].…”
Section: Uv-vis Absorption and Ecd Spectroscopic Studysupporting
confidence: 85%
“…The distinctive changes in UV-ECD support our observations in the Soret spectral region that TMPyP interacts with (dA-dT) 10 by at least two binding modes: in addition to external binding mode to the phosphate backbone, which does not change the oligonucleotide structure significantly, another binding mode took place (for example an edge-on minor groove or a major groove binding took place as was suggested in [18]) which disturbs the arrangement of oligonucleotide bases [6]. Indeed, at the ratio 6/1, the UV-ECD spectrum reflects the transition state between B-and modified Z-forms of the (dA-dT) 10 [17].…”
Section: Uv-vis Absorption and Ecd Spectroscopic Studysupporting
confidence: 85%
“…The MCD signals of NiPzP changed from a genuine (+) A-term to a (-) pseudo-A-term upon interaction with poly(dG-dC) 2 . Such change was also observed for binding of Pd(II)TMPyP to poly(dG-dC) 2 [26]. The negative band appeared at 405 nm (∆ε/M = -10.3 T -1 ; Table 2); however, the positive band at longer wavelength could not be observed clearly.…”
Section: Spectroscopic Evidence For Porphyrin-dna Interactionssupporting
confidence: 58%
“…It has also been shown that the binding mode of porphyrins to the nucleic acid duplex, e.g. intercalative or outside binding mode, can also be tuned by varying the metal center and the thickness of the complex molecule based on the presence or absence of axial ligands [13,[23][24][25][26][27]. Thus, the thin square planar copper(II) derivatives of H 2 TMPyP and H 2 PzP are capable of intercalation, because these metalloporphyrins are not ligated at their vacant axial site by aquo ligands and can intercalate into the pocket between two adjacent, closely spaced (3.4 Å) base pairs of B-DNA.…”
Section: Introductionmentioning
confidence: 99%
“…It is of advantage to next examine the CD and reported FLD r data and relate them to our MCD conclusions. First, the large amplitude of the (+) CD band (λ 0 CD = 444 nm, Δε 0 = +32 cm -1 M -1 ) is definitive for groove binding, which is in contrast to much weaker CD bands observed in cases of weak “nonspecific” outside binding (wnob), e.g., Δε ∼ 1.5 cm -1 M -1 in PdP(2) /poly(G-C) 2 . Second, the (+) CD sign would tentatively be assignable to edge-on minor groove binding (AT-rich segments 14 ) with one drug edtm, μ e D (either μ ex D or μ ey D of the porphyrin's orthogonal edtm pair), having orientation angles α/β/β‘ = ∼45°/0°/90° .…”
Section: Resultsmentioning
confidence: 98%